Effect of low-dose X-ray irradiation on micronucleus formation in human embryo, newborn and child cells. (1st December 2016) - Koyama, Shin; Narita, Eijiro; Shinohara, Naoki; Miyakoshi, Junji
Abstract: Purpose: It is well known that a high-dose of ionizing radiation is sufficient to break DNA strands, which leads to elevated genotoxic risks; however, the risks associated with low doses of ionizing radiation remain unclear. In addition, there is little data about the effect of low-dose ionizing radiation on human-derived embryo, newborn and child cells. We investigated the frequency of micronucleus (MN) formation in these cells to understand the genotoxic effects of ionizing radiation. Materials and methods: We irradiated the cells with X-rays from 0.02–2 Gy at a rate of 0.0635 Gy/min. After irradiation, we investigated the effect of low-dose X-ray irradiation on cellular viability and frequency of MN formation. Results: Increases in MN formation were largely dose-dependent; however, there were no differences between controls and doses lower than 0.2 Gy, except in KMST-6 human transformed embryo cells. Conclusion: We could not detect an obvious effect of low-dose X-ray irradiation at doses lower than 0.1 Gy. The embryonic cells were more sensitive to X-ray irradiation than newborn and child cells. The threshold for X-ray-induced MN formation appears to be in the range of 0.05–0.1 Gy in cultured human embryo, newborn and child cells.